A systematic review exploring the reflective accounts of applied sport psychology practitioners - Wadsworth, N.; McEwan, H.; Lafferty, M.; Eubank, M.; Tod, D. (International Review of Sport and Exercise Psychology, 2021)
This systematic review explores the reflective accounts of applied sport psychology practitioners. The aim of this review was to synthesise the reflective accounts of applied sport psychology practitioners and highlight common themes that provide focus to their reflective practice. The insight into current progress on reflective content in applied sport psychology provides a foundation to build on as we continue to understand this topic. Following a systematic search of the literature, a total of 73 studies were included within the review, which were analysed using thematic content analysis. Analysis of the reflective accounts resulted in the creation of nine higher-order themes: Process and Purpose of Reflective Practice; Ethical Practice; Supporting Person and Performer; Practitioner Individuation; Relationships with Clients; Cultural Awareness; Competence-Related Angst; Support of Practitioner Development; and Evaluating Practitioner Effectiveness. The review includes recommendations for future research, such as the use of narrative analysis to provide further insight into applied practitioners` experiences. We also provide practical implications, which are tailored to match the specific demands of practitioners at different stages of development and include increased engagement in critical reflection for trainee practitioners and engaging with `critical friends` to facilitate the process of meta-reflection for newly qualified practitioners.